Data relating to "Regularised non-uniform segments and efficient no-slip elastohydrodynamics". - Walker, B; Gaffney, E (University of Oxford, 2021)
Data relating to "Regularised non-uniform segments and efficient no-slip elastohydrodynamics", including MATLAB scripts and data to generate all figures.